Jupiter's Ion Radiation Belts Inward of Europa's Orbit. Issue 4 (8th April 2021) - Kollmann, P.; Clark, G.; Paranicas, C.; Mauk, B.; Roussos, E.; Nénon, Q.; Garrett, H. B.; Sicard, A.; Haggerty, D.; Rymer, A.
Abstract: Jupiter is surrounded by intense and energetic radiation belts, yet most of the available in‐situ data, in volume and quality, were taken outward of Europa's orbit, where radiation conditions are not as extreme. Here, we study measurements of ions of tens of keV to tens of MeV at <10 Jupiter radii ( R J ) distance to Jupiter, therefore inward of the orbit of Europa. Ion intensities drop around 6  R J, near Io's orbit. Previous missions reported on radiation belts of tens and hundreds of MeV ions located between 2 and 4  R J . Measurements of lower energies were not conclusive because high energy particles often contaminate the measurement of lower energy particles. Here, we show for the first time that ions in the hundreds of keV range are present and suggest that ions may extend even into the GeV range. The observation of charged particles yields information on the entire field line, not just the local field. We find that there is a region close to Jupiter where no magnetic trapping is possible. Jupiter's innermost radiation belt is located at <2  R J, inward of the main ring. Previous work suggested that this belt is sourced by re‐ionized energetic neutral atoms coming steadily inward from distant regions. Here, we perform a phase space density analysis that shows consistency with such a local source. However, an alternative explanation is that the radiation belt is populated by occasional strong radial transport and then decays on the timescale of years. Plain Language Summary: Planets with a magnetic field, like Earth and Jupiter, are surrounded by belts of natural charged particle radiation. These regions are called "radiation belts, " and they pose challenges to space exploration because of their severe effects on spacecraft and humans. Understanding the fundamental nature of radiation belts, for example, formation, structure, and dynamics has also been a scientific pursuit for decades, but there is still much to learn. Some of the most extreme radiation conditions are found at Jupiter, which makes that planet an ideal laboratory to study how radiation develops in space. Even though raw measurements from satellites in orbit of Jupiter exists, they often cannot be used as‐is. This is because strong radiation can interfere with radiation instruments in the same way that direct sunlight interferes with a thermometer. Here, we present results of a careful processing of data from the Juno mission to get around the instrument limitations. Our analysis not only extends the observed energy ranges of ions of Jupiter radiation belts but also forms the basis for testing new ideas. For example, our results suggest that the belts may form by ions that originate from a different region around Jupiter. Key Points: Ion belts at a distance of 2–4 Jovian radii have significant intensities from hundreds of keV to GeV Phase space densities of the innermost ion belt suggest non‐steady state conditions or a local source A region without stable magnetic trapping exists close to Jupiter